Representation of Islamic Communication in Multicultural Spaces: A Semiotic Analysis of the Film 99 Cahaya di Langit Eropa - Marhamah; Fauzi (Wardah, 2025)
This study aims to analyze the representation of Islamic communication within multicultural spaces through the film 99 Cahaya di Langit Eropa. The focus is directed toward visual symbols such as mosques and the hijab, verbal signs in the form of dialogues about Qur’anic recitation and greetings of peace, as well as the narrative of the main character’s religious experiences that portray interactions between Muslims and European society. The method employed is qualitative with Roland Barthes’ semiotic approach, which interprets signs through three layers: denotation, connotation, and myth. Data were obtained through documentation by repeatedly viewing the film and supported by academic literature related to Islamic communication, the mediatization of religion, and semiotics. The findings reveal that the film represents Islamic communication in a persuasive, inclusive, and adaptive manner, functioning as a medium of intercultural and interreligious interaction. At the denotative level, Islamic symbols appear as religious identity, while at the connotative level, they affirm values of tolerance, harmony, and solidarity. At the mythic level, the film constructs an ideological narrative that Islam is a universal religion capable of engaging in dialogue with diversity. This study highlights the significant role of popular media in constructing discourses of Islamic communication within multicultural spaces.